From an image to a text description of the image - Thian, Ronald Chuan Yan (2017)
This project presents an implementation of a search function that allows users to search for a particular object of interest using only textual information. The main idea is to train a very deep neural network architecture that generates a useful description for the video frame. Also, the focus is heavily emphasised on exploring different types of image captioning models and their differences. Network used consists of a Convolutional Neural Network (CNN) that learns features on an image, and a Long Short-Term Memory (LSTM) unit that is used to predict the sequence of words from the learnt features in the CNN. This project does not implement live captioning of videos but pre-processes the video into frames and generates the appropriate captions for each frame, before the user is able to conduct the textual search.